The p97–Ataxin 3 complex regulates homeostasis of the DNA damage response E3 ubiquitin ligase RNF8 - Singh, Abhay Narayan; Oehler, Judith; Torrecilla, Ignacio; Kilgas, Susan; Li, Shudong; Vaz, Bruno; Guérillon, Claire; Fielden, John; Hernandez‐Carralero, Esperanza; Cabrera, Elisa; Tullis, Iain DC; Meerang, Mayura; et al. (The EMBO journal, 2019)
The E3 ubiquitin ligase RNF8 (RING finger protein 8) is a pivotal enzyme for DNA repair. However, RNF8 hyper‐accumulation is tumour‐promoting and positively correlates with genome instability, cancer cell invasion, metastasis and poor patient prognosis. Very little is known about the mechanisms regulating RNF8 homeostasis to preserve genome stability. Here, we identify the cellular machinery, composed of the p97/VCP ubiquitin‐dependent unfoldase/segregase and the Ataxin 3 (ATX3) deubiquitinase, which together form a physical and functional complex with RNF8 to regulate its proteasome‐dependent homeostasis under physiological conditions. Under genotoxic stress, when RNF8 is rapidly recruited to sites of DNA lesions, the p97–ATX3 machinery stimulates the extraction of RNF8 from chromatin to balance DNA repair pathway choice and promote cell survival after ionising radiation (IR). Inactivation of the p97–ATX3 complex affects the non‐homologous end joining DNA repair pathway and hypersensitises human cancer cells to IR. We propose that the p97–ATX3 complex is the essential machinery for regulation of RNF8 homeostasis under both physiological and genotoxic conditions and that targeting ATX3 may be a promising strategy to radio‐sensitise BRCA‐deficient cancers. Synopsis The RNF8 ubiquitin ligase is a key mediator of the ubiquitin‐mediated DNA damage response and regulator of double strand break repair pathway choice. Here, these roles are shown to depend on homeostatic regulation of RNF8 by the ubiquitin‐dependent segregase p97/VCP and the deubiquitinase Ataxin 3 (ATX3). A p97‐ATX3 complex maintains proteasome‐dependent RNF8 homeostasis under physiological condition. The p97‐ATX3 complex extracts RNF8 from chromatin after its recruitment to DNA damage sites. p97‐ATX3‐mediated RNF8 extraction promotes timely RNF168 recruitment and utilization of non‐homologous end joining (NHEJ) repair. Inactivation of the p97‐ATX3 complex hyper‐sensitizes BRCA2/homologous recombination‐deficient cells to ionizing radiation. Graphical Abstract Chromatin extraction of RNF8 by the ubiquitin‐dependent segregase p97/VCP and the deubiquitinase ATX3 emerges as a key mechanism for balancing DNA repair pathway choice.